2022
DOI: 10.1021/acssuschemeng.2c00028
|View full text |Cite
|
Sign up to set email alerts
|

Surface Science in the Research and Development of Hydrate-Based Sustainable Technologies

Abstract: Compact gas inclusion in hydrates presents not only fascinating science but also wide-ranging applications in sustainable energy and environmental technologies. The surface of hydrates dictates many essential phenomena underlying hydrate-based processes such as hydrate nucleation and growth, mass transfer, heat transfer, agglomeration, adhesion, and adsorption. Thus, surface science falls within the core of hydrate science and engineering. This paper covers an insight perspective on surface science related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 224 publications
0
19
0
Order By: Relevance
“…Certainly, any hydrate in a micropore must occur into a subunit-cell state, which raises a fundamental question concerning whether the hydrate structure could be confined to a subunit-cell scale. Moreover, theoretical predictions , and experiments have shown that hydrate structures are thermodynamically destabilized under high confinements, which means that gas hydrate formation in highly confined spaces (i.e., micropores) experiences thermodynamic inhibition effects similar to those in saline solutions. These factors must be taken into consideration for elucidating confined gas hydrates.…”
Section: Working Mechanisms Of Nanoreactorsmentioning
confidence: 99%
See 4 more Smart Citations
“…Certainly, any hydrate in a micropore must occur into a subunit-cell state, which raises a fundamental question concerning whether the hydrate structure could be confined to a subunit-cell scale. Moreover, theoretical predictions , and experiments have shown that hydrate structures are thermodynamically destabilized under high confinements, which means that gas hydrate formation in highly confined spaces (i.e., micropores) experiences thermodynamic inhibition effects similar to those in saline solutions. These factors must be taken into consideration for elucidating confined gas hydrates.…”
Section: Working Mechanisms Of Nanoreactorsmentioning
confidence: 99%
“…Strong solid–water binding pulls interfacial water molecules toward the solid surface, inducing a collapse of the interfacial water network into a distorted and high-density configuration equivalent to a compression effect . This density fluctuation of water decays rapidly along the surface normal and vanishes at a distance of around 1 nm from the solid surface, even though the collapse of the water network could extend to a distance of many nanometers from the solid surface. , This structurally mismatched layer is also known as the interfacial premelting layer. , Therefore, strongly hydrophilic (or charged) solid surfaces induce a distortion of the interfacial water structure that cannot be a seeding structure for the nucleation of gas hydrates. Consistent with this conclusion, computer simulations have shown that no gas hydrate cages could exist in the premelting layer next to highly hydrophilic (or charged) solid surfaces. , On the other hand, highly hydrophobic solid surfaces interact weakly with interfacial water through van der Waals (vdW) forces.…”
Section: Working Mechanisms Of Nanoreactorsmentioning
confidence: 99%
See 3 more Smart Citations